Puberty and the Manifestations of Loss of Control Eating in Children and Adolescents - Vannucci, Anna (2014)
OBJECTIVE: We investigated the manifestations of pediatric loss of control (LOC) eating at different stages of pubertal development. METHODS: Participants were a non-clinical sample of 468 youth (8–17y). Physical examination determined pubertal stage. LOC eating and disordered eating attitudes were assessed with the Eating Disorder Examination. In a randomized crossover design, a subset (n=244) ate ad libitum from two test meals designed to capture normal and LOC eating. RESULTS: There were no differences in the prevalence rates or frequency of reported LOC eating episodes across pubertal stages (ps≥.50). There were, however, puberty by LOC eating interactions in disordered eating attitudes and palatable food consumption (ps≤.05), even after adjusting for age and body composition. LOC eating was associated with elevated global disordered eating attitudes, weight concern, and shape concern in post-pubertal youth (ps≤.001), but not pre-pubertal youth (ps≥.49). In late-puberty, youth with LOC eating consumed less energy from protein (p<.001) and more from carbohydrate (p=.003) and snack-type foods (p=.02) than those without LOC eating, whereas endorsement of LOC eating in pre- or early-to-mid-puberty was not associated with differences in eating behavior (ps≥.20). CONCLUSIONS: Findings suggest that puberty may be a critical risk period, when LOC eating behaviors in boys and girls may become accompanied by greater weight and shape concerns and more obesogenic food consumption patterns. Interventions for LOC eating during pre-puberty should be evaluated to determine if they are particularly beneficial for the prevention of exacerbated eating disorder psychopathology and adverse weight outcomes.